The Strengths Perspective and Persons with Substance Abuse Problems - Rapp, Richard C. (CORE Scholar, 2002)
This chapter is from the book The Strengths Perspective in Social Work Practice, which presents an unrivaled collection of essays, explains the strengths-based philosophy, demonstrates how it works, and provides clear and practical tools for its application. This third edition includes four new chapters, including subjects such as spirituality and disability; oppression and the strengths of the cultures of First Nations peoples; discovering the strengths of social workers in working with grass-roots welfare movements; and a new look at resilience, children, and community. In addition, many other chapters have been significantly updated with new references, new case vignettes, and new research. The study questions have been revised to reflect the changing knowledge in the field. This is possibly the most extensive and varied text in the rapidly expanding field of strengths literature.